REVIEW ARTICLE: PENGARUH POLIMER PADA SISTEM PENGHANTARAN OBAT TRANSMUKOSAL - Nia Yuniarsih; Mentari; Elista Indah Susanti; Ainun Mar’atus Putri Warsito; Refriyanti Irma; Muhamad Zein Latif (Jurnal Buana Farma, 2024)
Currently, drug delivery systems have been widely researched and developed to enable increased bioavailability by regulating drug release. One of the factors in drug release is a composite polymer which is needed as a protective matrix for the delivery system with the aim of drug stability. One of the drug delivery targets is transmucosal. This review article aims to find out the role of various polymers in transmucosal drug delivery systems. The method used for information is the results from the ScienceDirect, PubMed, Google Scholar, ResearchGate and WoS (Web of Science) databases. The results show that CMC-Na, HPMC, chitosan, pectin, Carbopol, Acebutolol HCL, maintains the duration of the drug's residence time after the absorption process because the polymer has adhesive power.